Renal and Splenic Infarction: Unusual Manifestation of the Antiphospholipid Syndrome - Daher, Elizabeth F; Lima, Rafael S.A.; Melo, Ana Cristina L.; Silva Junior, Geraldo B (Journal of Medicine, 2014)
<!–[if gte mso 9]> <![endif]–> Antiphospholipid syndrome is a multisystem disorder characterized by recurrent thromboses in the arterial system, venous system, or both. A 42-year-old man sought treatment reporting two episodes of abdominal pain in the right flank radiating to his back associated with nausea and vomiting fifteen days prior to admission. Abdominal CT with contrast showed left renal atrophy, renal right and splenic infarction. Laboratory tests showed worsening of renal function after CT contrast: serum creatinine 0.6mg/dL to 5.5mg/dL. The complementary investigation showed anti-cardiolipin antibodies (aCL) positive in high titers; antinuclear antibodies, myeloperoxidase-antineutrophil cytoplasmic antibody, anti-nuclear antibody, serology for hepatitis A, B and C, ELISA anti-HIV and VDRL were negative. A diagnosis of renal and splenic infarction due to antiphospholipid syndrome was made and the patient received treatment with subcutaneous heparin followed by warfarin. DOI: http://dx.doi.org/10.3329/jom.v14i2.19672 J Medicine 2013, 14(2): 187-188 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE BN <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>